2000
DOI: 10.1111/j.1530-0277.2000.tb04650.x
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Morbidity of Alcohol Use Disorders in the Center of France

Abstract: This exhaustive study demonstrates the degree of alcohol-related morbidity among hospitalized patients, which is particularly high in men, in the Auvergne region of France. The study emphasizes the lack of diagnosis, particularly for the young, and the apparent deficiencies in the hospital management of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 13 publications
(12 reference statements)
1
6
1
Order By: Relevance
“…The similarity of results from preventive medicine services and specialized treatment services showed the difficulty of establishing predictors of use and abuse of alcohol and psychotropic substances (Inserm, 2003;Reynaud et al, 2000). Trends in the evolution of psychoactive substance consumption are confirmed.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…The similarity of results from preventive medicine services and specialized treatment services showed the difficulty of establishing predictors of use and abuse of alcohol and psychotropic substances (Inserm, 2003;Reynaud et al, 2000). Trends in the evolution of psychoactive substance consumption are confirmed.…”
Section: Resultsmentioning
confidence: 73%
“…A cross-sectional survey performed on one given day in a French hospital, in the centre of the country (Reynaud, Malet, Facy, & Glanddier, 2000), showed that 20% of hospitalized patients (all causes) drink excessively. An analysis restricted to 16-to 25-year-old hospitalized patients shows that 25% of men have excessive alcohol consumption compared to less than 10% of women.…”
mentioning
confidence: 99%
“…It is also clear that the hospital system is not dealing adequately with the problem of addiction [2]. Twenty per cent of hospitalized patients and 10% of patients who use emergency services have a drinking problem.…”
Section: The Shift From 'The Fight Against Alcoholism' To Addictions mentioning
confidence: 99%
“…Hence, early screening and brief interventions in addition to early medical and social interventions became justified, especially in young multiple drug users [2][3][4].…”
Section: The Shift From 'The Fight Against Alcoholism' To Addictions mentioning
confidence: 99%
“…Approximately 20% of patients seen in clinical practice have an underlying alcohol-use disorder (1 ). In the last 20 years, specialist work on alcohol misuse has focused mainly on diagnosis at the dependence stage.…”
Section: To the Editormentioning
confidence: 99%